MSC virtual e-abstract (CPP-01) - Stroke Conference 2020, Malaysia (Journal Of Cardiovascular, Neurovascular & Stroke, 2020)
1. Stroke and tocotrienols unique role in neuroprotection (saturn): Protocol. 2. Age on prevalence of epidemiological factors, stroke subtypes and stroke events: An observational study. 3. Intravenous thrombolysis in older patients with acute ischaemic stroke. Is it safe in older patients in Malaysia?. 4. Intravenous and intra-arterial thrombolysis for ais with wake-up stroke – A case report from Sarawak General Hospital. 5. Thrombolysis in hyperacute stroke by physicians in resource-limited settings: The establishment of service and clinical outcome appraisal. 6. Outcome of ischemic stroke thrombolysis treatment in Seberang Jaya Hospital, A single center 8 years review: 2012- 2019. 7. Retrospective comparison of hyperacute mri brain vs. Ct brain in acute ischemic stroke : An observational study in a district hospital.